Exploring the first-hand experiences of adult males diagnosed with high functioning autism during their adulthood - Lupindo, Marinos Bomikazi (Department of Psychology, 2020)
This study aimed to explore the first-hand experiences of adult males diagnosed with high-functioning autism during their adulthood. Particularly, it aimed to explore the nature of their initial presenting symptoms, gender-related factors that contribute to adulthood diagnosis of autism in males, the challenges they experienced prior to and succeeding their diagnosis, and lastly, the impact that receiving a late diagnosis had on their overall early development. This study applied the exploratory qualitative research design as a method of inquiry. Participants recruited were current (during the time the study was conducted) clients at the Neurodiversity Centre and ten participants were selected using the purposive sampling technique. An interview schedule with open-ended questions was used as a guide to collect data on participants’ life histories. To analyze the findings, the thematic analysis technique was used in conjunction with the NVivo 12 qualitative analysis software; which was used to assist in organizing the data and identifying the themes. The findings of this study highlighted four key features of the experiences of males diagnosed with high functioning autism during adulthood. It was evident that initial presenting symptoms were noticeable during early childhood, however, various factors resulted in these challenges being misinterpreted or overlooked. This lack of a formal diagnosis is perceived to have impacted the participants’ early life in various ways forcing them to navigate through life without an understanding of their difficulties. Without these challenges being adequately addressed and understood, participants felt forced to adapt and find coping strategies (some of which were maladaptive) to navigate through life and maintain some sort of “normalcy”. It was evident that succeeding their diagnosis, the lack of support services and guidance for adults with autism left the participants feeling that the future does not look any brighter than the past. To the researcher’s knowledge, this study was the first (within the African context) to explore the experiences of adults with Autism Spectrum Disorder (ASD). With this being said, these findings highlight the importance of creating more knowledge and understanding, for professionals and the general public, around the experiences of adults with autism, as these individuals encounter major life challenges (especially without a formal diagnosis) and urgently need support, both professionally and personally, in managing their difficulties.